Epileptic Phenotype and Cannabidiol Efficacy in a Williams–Beuren Syndrome Patient With Atypical Deletion: A Case Report - Nicotera, Antonio G.; Spanò, Maria; Decio, Alice; Valentini, Giulia; Saia, Maria; Di Rosa, Gabriella (Frontiers in Neurology, 2021)
Epilepsy is a rare clinical manifestation in Williams-Beuren syndrome patients. However, some studies report the presence of infantile spasms and epilepsy in patients carrying larger deletions. Herein, we describe a 13-year-old female affected by Williams-Beuren syndrome and pharmacoresistant epilepsy reporting a de novo large heterozygous 7q11.21q21 deletion (19.4 Mb) also including YWHAG gene. Studies indicate that Cannabidiol is effective as adjunctive therapy of seizures associated with Tuberous sclerosis complex, and it is under investigation also in Focal cortical dysplasia. When treated with Cannabidiol, our patient showed a significant reduction in seizure frequency and intensity, and improved motor and social skills. We hypothesized that CBD could be able to exert a gene/disease-specific effect.